Socioeconomic patterns of American farmland preservation funded by the Farm and Ranch Lands Protection Program - Stoms, D. M.; DeAngelo, G. (Journal of Conservation Planning, 2010)
Since 1996 the federal Farm and Ranchland Protection Program (FRPP) has supported local programs to preserve their farmland by providing matching funds to "eligible cooperating entities." This paper analyzes where those funds have been distributed and then asks what kinds of communities choose to preserve farmland (i.e., become eligible cooperating entities) and which do not? And how widespread is farmland preservation likely to become in the near future? To answer these questions we compiled historical county-level spatial data on demographics, economics, agricultural, and GIS-based growth pattern statistics to characterize counties that have implemented farmland preservation programs as represented in FRPP allocations. Statistical models determined the probability that a county has received funding and predicted the level of funding. Applying the regression coefficients to contemporary data then forecast the level of funding expected in the coming decade if sufficient funds are available; that is, where current socioeconomic conditions now match the historic conditions that favored preservation at the initiation of the FRPP. The most significant variables of FRPP activity in counties were a combination of socioeconomic factors for the county as a whole (per capita income, population growth in the preceding decade), agricultural factors (area of farmland, direct sales of products to individuals in dollars), and a synthetic GIS-based index of sprawl. Although FRPP cannot distribute funds based on predicted "demand", prospective farmland preservationists may be inspired to act if they see that their county has characteristics similar to those that have already succeeded in meeting FRPP eligibility criteria.
Keywords: agricultural conservation easements; Farm and Ranchland Protection Program; FRPP; land trusts; local food movement; sprawl; urban growth